THE IMPACT OF TOURISM, SPORTS TOURISM AND OTHER SELECTIVE FORMS OF TOURISM ON EMPLOYMENT IN SARAJEVO CANTON - Amer Hodžić; Tarik Huremović (Sport Scientific And Practical Aspects, 2025)
Today, tourism represents a strong and important economic branch, whether it concerns economically developed and underdeveloped countries as well as developing countries. It can increase employment in almost all countries, regardless of their level of development. Today’s moment is marked by pronounced global crises, which again have a strong negative impact on the economic and social aspects of society, both globally and locally. Tourism, due to its characteristics and the positive effects it achieves in the process of realizing all activities in its area, can greatly reduce the percentage of unemployment in local communities. This positive effect of reducing unemployment is reflected in the possibility of employment for all categories of the unemployed, and particularly vulnerable groups of the unemployed such as people with disabilities, women, young people, the long-term unemployed, etc. Encouraging tourism in states or certain regions can have a favourable positive effect on employment within the territory. the same. For countries and regions that have developed tourism and that do not have pronounced problems with unemployment, activities through tourism increase the country’s balance of payments as additional income through exports. Underdeveloped regions and countries and developing countries, by increasing activities through tourism, in addition to being an important source of income, realize a particularly important positive effect through the reduction of unemployment rates in them. Many developed countries, among which Austria is the leader, as a highly developed tourist destination for a long time, institutionally, have realized and use the potential offered by tourism to increase employment and actively use it to reduce the unemployment rate. Unfortunately, in our country and its tourist regions, where tourism is often one of the most important economic branches, this has not been done and they still record high rates of unemployment. Tourism in Bosnia and Herzegovina and Sarajevo Canton is a sector that can make a significant contribution to faster economic development. In our country and its regions and cantons, there are great potentials for increasing tourism activities, which will generate a greater number of jobs in tourism as well as tourism-related economic branches. To successfully solve the problem of unemployment in Bosnia and Herzegovina, its regions and cantons, positive experiences of tourism development through selective forms of tourism can be used, also using models of successful experiences from the world and the countries of the European Union..